A gulf-wide synoptic isoscape of zooplankton isotope ratios reveals the importance of nitrogen fixation in supporting secondary production in the central Gulf of Mexico - Hernández-Sánchez, Oscar Gabriel; Camacho-Ibar, Víctor F.; Barbero, Leticia; Herguera, Juan Carlos; Herzka, Sharon Z. (Frontiers in Marine Science, 2023)
A synoptic gulf-wide isoscape of carbon (δ13C) and nitrogen (δ15N) in the Gulf of Mexico based on mesozooplankton (335-1000 um) was used as a proxy for the isotopic baseline and for calculating regional contributions of dissolved inorganic nitrogen sources. Mesozooplankton were sampled at 0-200 m (depth permitting) during the XIXIMI-06 and GOMECC-3 cruises held during the summer of 2017. A striking latitudinal gradient was found in δ15N values of zooplankton, with the highest values (10.4 ± 1.2‰) found over the northern shelf, and lowest values in the central, oligotrophic gulf (1.9 ± 0.5‰). To estimate the fractional contribution of potential nitrogen sources, the gulf was divided into six regions based on the spatial distribution of surface Chl-a, SST from remote sensing products and likely region-specific source contributions. A literature survey of (δ13C and δ15N values of particulate organic matter was used to characterize region-specific endpoint isotope ratios for use in a Bayesian isotope mixing model. Regional differences in δ15N values and the results of mixing models indicated nitrogen fixation is most likely an important source (45-74% contribution) of new nitrogen in the oceanic regions of the Gulf, the Loop Current and the Yucatan Shelf. In the oligotrophic gulf, the potential input of relatively light nitrate that reflects remineralization of surface layer POM or the excretion of light nitrogen by heterotrophs was insufficient to explain the low δ15N values found in the central Gulf, although it could account for about 40% of the N supporting secondary production. The high nitrogen isotope ratios found in the northern shelf were attributed to denitrified N (60%) and the inflow of heavy nitrogen from the Mississippi-Atchafalaya river system. Our results support the potential importance of fixed nitrogen in the deep waters of the Gulf of Mexico during the summer, characteristic for its highly stratified surface waters.